Law Enforcement on The Case Of Setting The Score in Soccer Competition (Comparative Study in Indonesia, Netherland, and Italy) - Vitrona Adhe Waditra; Rahtami Susanti; Bayu Setiawan (Faculty of Law Universitas Muhammadiyah Purwokerto, 2021)
Setting scores in football matches often occur whether coaches, players, or match officials do it. Several countries such as Italy, the Netherlands, and Indonesia already have regulations containing legal sanctions for these practices. This study used a normative juridical method obtained through a literature review, then analyzed qualitatively normative. This study aims to determine the law enforcement of scoring cases in soccer matches in Indonesia, the Netherlands, and Italy. The results showed that scoring arrangements in Indonesia could be acted upon under Law No. 20 of 2001 on amendments to Law No. 31 of 1999 concerning the Eradication of Corruption, while in the Netherlands, it used Wetboek van Strafrecht (Criminal Code) article 326, and in Italy regulated in Legge 13 dicembre 1989 n.401: truffa sportiva.Keywords: Score Setting, Football.